2012
DOI: 10.3389/fncom.2012.00017
|View full text |Cite
|
Sign up to set email alerts
|

Shortest Loops are Pacemakers in Random Networks of Electrically Coupled Axons

Abstract: High-frequency oscillations (HFOs) are an important part of brain activity in health and disease. However, their origins remain obscure and controversial. One possible mechanism depends on the presence of sparsely distributed gap junctions that electrically couple the axons of principal cells. A plexus of electrically coupled axons is modeled as a random network with bi-directional connections between its nodes. Under certain conditions the network can demonstrate one of two types of oscillatory activity. Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…A conceptual understanding of how re‐entry can work in a complicated network that contains multiple cycles comes from the work of Vladimirov et al . () and Singh et al . () (see also Gansert et al ., ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A conceptual understanding of how re‐entry can work in a complicated network that contains multiple cycles comes from the work of Vladimirov et al . () and Singh et al . () (see also Gansert et al ., ).…”
Section: Discussionmentioning
confidence: 91%
“…actually succeeds in establishing re‐entry. We see that one step of propagation is present (into cells 116 and 133), but do not show the precise complete path that leads to a successful return to cell 98 – a matter of some complexity (see Vladimirov et al ., ). Computational analysis of the present network structure showed that there are 2698 distinct cycles that contain both hub cell 68 and hub cell 98; thus, there are many possibilities available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the presence of multiple varicosities that are distributed in an ‘ en passant ’, bead-on-a-string manner along thin axonal branches as well as axonal branching are expected to significantly impact on axial conduction and, thus, to modify signal propagation within the network. Also, the formation of nested-loop axonal trajectories in the infarct border zone may promote high-frequency electrical reentry within the local network, giving rise to abnormal sympathetic signaling (Vladimirov et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…In [23], the authors use a pyramidal cell model and also an excitable cellular automata model to study the possibility of high-frequency oscillations in randomly connected graphs. Their random graphs employ scalefree networks where the degree of each node is slightly less than 2.…”
Section: Discussionmentioning
confidence: 99%